Student and Teacher Partnership in the Study of Tiger Grass Industry in Marigondon Norte, San Andres, Romblon: Lessons for Novice Researchers - Fetalvero, Eddie; Faminial, Tomas (Romblon State University Research Journal, 2011)
This paper documents the struggle of authors as novice researchers, who although armed with high energy and spirit, almost lost heart to finish the project because of some issues they had to address and which they learned of only during the actual research experience.